Tin-catalyzed urea alcoholysis with β-citronellol: a simple and selective synthesis of carbamates - Silva, Márcio José da; Morais, Diego Chaves (Catalysis Letters, 2016)
Tin(II) chloride is a stable and water tolerant Lewis acid, commercially available and less corrosive than Brønsted acid catalysts. Our proposal was demonstrated that SnCl2 was an efficient catalyst on the urea alcoholysis with β-citronellol. We investigated the effects of main reaction parameters such as concentration and tin(II) catalyst nature, reagents stoichiometry and reaction temperature. In homogenous conditions with DMSO as solvent, the SnCl2-catalyzed urea alcoholysis reactions under air flux achieved high conversion and selectivity for β-citronellyl carbamate (ca. 90 and 95 %, respectively). Among tin(II) catalysts assessed, SnCl2 was more active due to its total solubility. Possible intermediates of active Sn(II) species were discussed based on the results of catalytic runs and FT-IR spectroscopy measurements of the liquid phase after the reaction. FT-IR spectroscopy data showed that the active species could be a complex of a Sn(II) atom coordinated with N=C=O. This novel and phosgene-free selective process provide an inexpensive and attractive route to synthesize terpenic carbamates through inexpensive and renewable reactant (i.e. urea). Moreover, SnCl2 was also an efficient catalyst on synthesis of β-citronellyl carbonate.
Keywords: Tin chloride; Urea; Terpenic alcohols; Carbamates